Development of stainless steel trolley - Nur Adilah, Ahmad (2008)
This report presents about trolley that always been used especially in lab. This trolley is a device which is important in order to ease transportation and to decrease the load when we want to lift or transport heavy items from one place to another. The idea of the fabricating of this trolley is based on student’s creativity. The selection of suitable materials in the fabricating of this trolley is a loaded material which has minimum weight, long life-span and can detain heavy load. Materials are proposed for the fabrication of the trolley is a stainless steel material. In this report, we’ll also be having more to the fabrication of this trolley.